Deployment of municipal solid wastes as a substitute growing medium component in marigold and basil seedlings production - Tzortzakis, Nikos G.; Gouma, Sofia; Paterakis, Costas; Manios, Thrassyvoulos (My University, 2012)
The possible use of municipal solid waste compost (MSWC) in the production of marigold and basil seedlings examined. Six medium prepared from commercial peat (CP) and MSWC (0, 15, 30, 45, 60, and 100% v/v). There was not any plant growth when MSWC used alone (100%). The addition of MSWC in low content (15% and 30%) improved seed emergence for marigold and basil respectively, while greater content revealed opposed impacts. Mean emergence time delayed as MSWC content increased into substrates. Addition of MSWC (especially in content greater than 30%) into CP reduced (from 34 to 64%) plant height, leaf number and stem diameter as a consequence reduced plant fresh weight (plant biomass) for both species. The number of lateral stems decreased (up to 81%) in basil when MSWC added into substrate mixtures. Chlorophyll b content decreased (up to 58%) in substrates with MSWC content greater than 15% or 30% while similar reduction observed in content of Chlorophyll a and total carotenoids for basil with MSWC > 60%. However, Chlorophyll a and total carotenoids content increased as MSWC content increased for marigold. K and Na leaf content increased but P equivalent decreased as MSWC content increased. Nursery-produced basil and marigold seedlings grown in 15% MSWC; displayed quality indices similar to those recorded for conventional mixtures of peat and may act as component substitute.
Keywords: Growing media; Peat; Growing medium